Genetic relationships within a population of Blue Duck Hymenolaimus malacorhynchos - Triggs, Susan; Williams, Murray; Marshall, Stephen; Chambers, Geoffrey (Wildfowl, 1991)
DNA fingerprinting revealed a very high degree of genetic similarity within a small population of Blue Ducks, supporting observations of limited dispersal. The three major family groups studied proved to be interrelated. One example of close inbreeding was confirmed and another suggested. All genetic relationships indicated by observational studies were confirmed by genetic data including correct parentage of ten broods. Thus, no evidence was found of multiple paternity or maternity in this territorial riverine species.